The Influence of Education Level and Labor Force Participation Rate (LFPR) on the Gender-Based Open Unemployment Rate in Aceh Province - Liza Syahwi; M. Rasyidin; M. Saleh (SAINTIS Publishing, 2026)
This study analyzes the influence of education level and labor force participation rate (LFPR) on the gender-based open unemployment rate in Aceh Province during the period 2015–2024. Using multiple linear regression (OLS), the study evaluates the structural relationship between education, labor participation, and unemployment while considering gender aspects. The estimation results indicate that education level has a significantly negative effect on open unemployment, while LFPR has a significantly positive effect. The coefficient of determination (R²) values of 0.63 for the male model and 0.8 for the female model suggest that education and LFPR variables can explain most of the variation in open unemployment rates in Aceh. The gender analysis reveals that although female labor participation is lower, their unemployment rate fluctuates more than that of males. The novelty of this study lies in its simultaneous gender-based regional analysis, which enriches the empirical literature on labor in Aceh. The findings recommend strengthening vocational education and implementing gender-responsive labor policies to reduce unemployment and narrow disparities in the labor market.